Analisis Faktor-Faktor yang Memengaruhi Terjadinya Turnover Karyawan pada PT X - Priambodo, Raden Irwan (Jurnal Bisnis dan Keuangan, 2018)
One form of behavior is the wish of employees the move (turnover intentions) that led to the decision employees to left his job. With the level of turnover to companies, will increase have a potential costs, whether it is the cost of training who have invested on employees, the performance that should be sacrificed, and the costs recruitment and training back. The purpose of this research is to know the factors that affect turnover employee who happened to PT X. This study used a quantitative approach. Quantitative the kind of research that is used on the thesis this is quantitative explorative. The population of this study is all former employees of PT X total of 145 employees. The sample used using formulas slovin which totaled 107 an employee with a method of purposive addition to random. Data collection method that is used is questionnaire and documentation The result of this research are six factors that becomes consideration respondents to get out of companies are compensation (factor of 1), career opportunity (factor of 2), employee opportunities elsewhere (factor of 3), personal growth and development (factors of 4), uncomfortable.work (factor of 5) and job dissatisfaction (factor of 6)